Variability of grass pollen allergy symptoms throughout the season: Comparing symptom data profiles from the Patient's Hayfever Diary from 2014 to 2016 in Vienna (Austria)() - Bastl, Maximilian (World Allergy Organ J, 2021)
BACKGROUND: Grass pollen allergy is the most widespread pollen allergy in the world. It still remains unknown in which aspects and in which extent symptoms from grass pollen allergy differ throughout the grass pollen season, although individual sensitization profiles of persons concerned are known for a long time. METHODS: The crowd-sourced symptom data of users of the Patient's Hayfever Diary were filtered for significant positive correlated users to grass pollen from Vienna (Austria) during the respective grass pollen seasons from 2014, 2015, and 2016. These symptom data were the foundation for 3 statistical approaches in order to examine different sections of the grass pollen season defined either by grass pollen data, phenology (grass species determination in the field), or symptom data itself. RESULTS: Results from all 3 approaches are similar and come to the same major conclusion. The symptom peak of most users is observed in the second section of the grass pollen season (70%), followed by the first section (20%), and with the least user numbers (10%) the third section. The profiles from single users entering data for all 3 years under study are robust and show a comparable behavior from year to year. CONCLUSION: Grass taxa such as Arrhenatherum, Festuca, and Lolium seem to induce the highest symptom severity in most users during the second section of the grass pollen season. Poa and Dactylis are the main triggers for the first section of the grass pollen season. The flower of Phleum und Cynodon is documented for the last section of the grass pollen season. Crowd-sourced symptom data is the prerequisite for personal pollen information to consider the individuality of grass pollen allergy sufferers. Phenological monitoring is needed to provide information on specific grass taxa of importance to allergic persons.